Author Correction: Reactive astrocytes function as phagocytes after brain ischemia via ABCA1-mediated pathway. Issue 1 (December 2017) - Morizawa, Yosuke; Hirayama, Yuri; Ohno, Nobuhiko; Shibata, Shinsuke; Shigetomi, Eiji; Sui, Yang; Nabekura, Junichi; Sato, Koichi; Okajima, Fumikazu; Takebayashi, Hirohide; Okano, Hideyuki; Koizumi, Schuichi
Abstract The original version of this Article contained an error in the spelling of the author Nobuhiko Ohno, which was incorrectly given as Noubuhiko Ohno. This has now been corrected in both the PDF and HTML versions of the Article.